2020
DOI: 10.15252/emmm.202012324
|View full text |Cite
|
Sign up to set email alerts
|

Kaposiform lymphangiomatosis effectively treated with MEK inhibition

Abstract: Kaposiform lymphangiomatosis ( KLA ) is a rare lymphatic anomaly primarily affecting the mediastinum with high mortality rate. We present a patient with KLA and significant disease burden harboring a somatic point mutation in the Casitas B lineage lymphoma ( CBL ) gene. She was treated with MEK inhibition with complete resolution of symptoms, near‐complete resolution of lymphatic fluid burden,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 8 publications
(11 reference statements)
2
62
0
1
Order By: Relevance
“…Importantly, the health of these two patients improved in response to trametinib, but not to sirolimus (28,31). The precise mechanism by which trametinib improved lymphatic function in these patients was not determined.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Importantly, the health of these two patients improved in response to trametinib, but not to sirolimus (28,31). The precise mechanism by which trametinib improved lymphatic function in these patients was not determined.…”
Section: Discussionmentioning
confidence: 93%
“…There is growing evidence that other complex lymphatic anomalies are associated with RAS pathway–activating mutations. Mutations in RASA1 ( 26 ), EPHB4 ( 27 ), ARAF ( 28 ), NRAS ( 29 , 30 ), and CBL ( 31 ) have been identified in complex lymphatic anomaly patients. Additionally, patients with Noonan syndrome with RAS signaling pathway mutations can have lymphatic dysplasia, lymphedema, and retrograde lymph flow ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting that MEK inhibitors may be effective in patients with KLA after NRAS mutations are detected, but there are currently no clinical trials. Furthermore, trametinib has been reported to be effective in the treatment of KLA patients without NRAS mutations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in recent years, somatic mutations underlying pathogenesis of vascular anomalies have been identified, including mutations in the phosphoinositide 3‐kinase (PI3K)/Akt/mTOR and RAS viral oncogene homolog (Ras)/mitogen‐activated protein kinase (MAPK) signaling pathways 29–32 . A Phase II study demonstrated that sirolimus is effective and safe for complicated vascular anomalies, 14 and other novel targeted therapies, including PI3K and mitogen‐activated protein kinase kinase (MEK) inhibitors are being evaluated in the clinical and preclinical setting 29–32 . In our cohort, only one patient received a targeted therapy, sirolimus, prior to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%